Implementasi Pembelajaran Berdiferensiasi Melalui Model Keterpaduan Tipe Connected untuk Menentukan Tingkat Kemampuan Berpikir Siswa - Mulyadi Maruni (Jurnal Didaktika Pendidikan Dasar, 2024)
Differentiated learning is learning that focuses on the individual differences of learners. Differentiated learning is designed to be effective and learner-centered. The connected model is a learning model to determine the level of thinking ability of students in implementing differentiated learning. This research aims to describe the effectiveness of the connected model so that it can be used in the learning process to determine the tingkat of thinking ability of students. Based on the results of the test of the effectiveness of the tingkat of thinking ability on a limited scale trial through the analysis of posttest scores, students experienced changes to reach the prestructural category 4.3%; unistructural 37.2%; multistructural 42.8%; while for relational 14.3%, and extended abstract by 1.4%. The data from the results of the broad-scale trial also showed an increase in the tingkat of thinking of students through the analysis of the posttest scores of students experiencing changes reaching the prestructural category by 10%; unistructural 47.5%; multistructural 35.8%; relational by 6.7%, while in the extended abstract category students did not reach the level of thinking. Based on the results of the study, the connected model can determine the level of thinking ability of junior high school students so that it is effectively used in differentiated learning.